TARJAMAH MAQTHA’ ADABY DAN PENINGKATAN KEMAMPUAN PENERJEMAHAN BAHASA ARAB - Laela Tinmah; Rifqi Aulia Rahman (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2018)
The purpose of this study was to determine the increase translate Arabic-Indonesia santri experimental group (the group that followed the learning by using tarjamah maqtha’ adaby) with a control group students (groups that follow the learning without the use of tarjamah maqtha’ adaby). This study was conducted from Desember to January 2018. The research is a quantitative research, the experimental method design using pretest-postest control group design. The population in this study were all students off class 3 Wustho in the Pondok Pesantren Al-Mabrur banjarnegara as many as 25 students. The data collection techniques performed by using observation, interview, documentation, and test. While the assesment instrument made by validity and reability testing. Data of final analysis result using gain test and t test. Result of analysis for experiment class obtained value 0,388 with medium criterion. While in the control class obtained value 0,308 with medium criteria. It shows an increase in the experimental class by using Tarjamah Maqtha’ Adaby technique. And t test with 5% T_ (count) = 2,807 and df = 23 obtained t_tabel = 2,069 for T_ (count) > t_tabel.